CORRECTION OF PSYCHOEMOTIONAL STATUS OF THE PATIENTS WITH BURNING MOUTH SYNDROME - E. N. Zhulev; N. V. Tiunova; L. M. Lukinyh (Кубанский научный медицинский вестник, 2015)
A study of the psychoemotional status of patients with burning mouth syndrome identified anxiety, fear, confusion, tension, emotional lability, cancerophobia varying degrees of severity. The authors have proved the efficiency of correction of psychoemotional status of the patients with burning mouth syndrome with the use of tenoten.